2007
DOI: 10.1182/blood.v110.11.518.518
|View full text |Cite
|
Sign up to set email alerts
|

High Survival Rate in Adult Burkitt’s Lymphoma/Leukemia and Diffuse Large B-Cell Lymphoma with Mediastinal Involvement.

Abstract: With short intensive chemotherapy mainly based on HDMTX, fractionated alkylators and HDAC outcome of Burkitt’s NHL and mature B-ALL (B-ALL) in adults could be improved substantially to CR rates of 80% and overall survival (OS) of 50–70% (Hoelzer et al, Blood, 1996). Further intensification - namely increase of MTX dose - failed to improve these results. Therefore the German Multicenter Study Group for Adult ALL (GMALL) invented in 2002 a new protocol for mature B-ALL/Burkitt and other high-grade NHL, namely pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
3
15
0
1
Order By: Relevance
“…In both HIV-positive and HIV-negative patients aged 55 years or older, the frequency of cytopenias was similar but the duration was lower, with fewer infections and mucositis, probably due to reduced intensity of chemotherapy given to these patients. The prognostic factors identified in this study (CNS and BM involvement and poor general status) are consistent with those identified in other trials [15][16][17][18][19][20][21][22][23][24][25][26][27][28] or in population-based studies 30 with the exception of advanced age. We have attributed the lack of poor prognosis in older patients to 2 features.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In both HIV-positive and HIV-negative patients aged 55 years or older, the frequency of cytopenias was similar but the duration was lower, with fewer infections and mucositis, probably due to reduced intensity of chemotherapy given to these patients. The prognostic factors identified in this study (CNS and BM involvement and poor general status) are consistent with those identified in other trials [15][16][17][18][19][20][21][22][23][24][25][26][27][28] or in population-based studies 30 with the exception of advanced age. We have attributed the lack of poor prognosis in older patients to 2 features.…”
Section: Discussionsupporting
confidence: 90%
“…15,16 The adaptation of these schedules to adults has led to an increase in the response rate and survival, ranging from 60% to 70% of cases in some series. 17 The addition of rituximab to these specific therapies may represent a step forward in the therapy of BL. Although no randomized trials on the use of rituximab have been published to date, and most of the studies are retrospective and include a limited number of patients, the tolerability and efficacy of specific immunochemotherapy seems to be good, with response rates between 70% and 90% and survival ranging from 70% to 80%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibody therapy is an attractive target to study in induction therapy for ALL. CD20 is expressed in 50-70% of pre-B ALL cells and there are preliminary data on the use of rituximab in the treatment of B-cell precursor ALL (Jandula et al, 2001;de Vries et al, 2004;Thomas et al, 2006a;Hoelzer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In 80-90% der Fälle weisen diese Leukämien/Lymphome eine CD20-Expression auf. Die Gabe von Rituximab vor den Chemotherapiezyklen hat zu einer deutlichen Verbesserung der Therapieergebnisse geführt [15].…”
Section: Therapie Der Reifzelligen B-allunclassified